2002
DOI: 10.1021/jf010887y
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Bovine β-Lactoglobulin and Peptides under Different Physicochemical Conditions

Abstract: The aim of this study was to determine if peptides could interact with beta-lactoglobulin (beta-LG) and what the physicochemical conditions promoting their interaction with the protein are. The binding of negatively charged (beta-LG 125-135 and 130-135), positively charged (beta-LG 69-83 and 146-149), and hydrophobic (alphaS1-CN 23-34 and beta-LG 102-105, both bioactive peptides) peptides to bovine beta-LG was determined using an ultrafiltration method under different physicochemical conditions: pH 3.0, 6.8, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Interactions between intact milk proteins (i.e. b-Lg) and milk protein-derived peptides have been studied by Noiseux, Gauthier, & Turgeon (2002). At pH 3.0, no peptide/b-Lg interactions were found, possibly because electrostatic repulsion prevented interaction between the positively charged b-Lg and the peptides studied.…”
Section: Potential Role Of Functional Properties Of Milk-derived Bioamentioning
confidence: 99%
“…Interactions between intact milk proteins (i.e. b-Lg) and milk protein-derived peptides have been studied by Noiseux, Gauthier, & Turgeon (2002). At pH 3.0, no peptide/b-Lg interactions were found, possibly because electrostatic repulsion prevented interaction between the positively charged b-Lg and the peptides studied.…”
Section: Potential Role Of Functional Properties Of Milk-derived Bioamentioning
confidence: 99%
“…This information could help understanding of the gelation mechanism in protein hydrolysates. In addition, previous studies have shown the ability of b-lg to interact with peptides (Barbeau, Gauthier, & Pouliot, 1996;Noiseux, Gauthier, & Turgeon, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Each BLG monomer consists of 162 residues (18.3 kDa) folded into eight stranded antiparallel β-sheets that form a hydrophobic pocket or calyx, flanked on one side by an α-helix [8] (Figure 1A and B). Although its biological function is uncertain [9], BLG is relevant to the food and pharmaceutical industries due to its ability to bind fatty acids, vitamins and peptides and it has been the subject of numerous biochemical and structural studies. For hydrophobic ligands two sites have been postulated: one inside the calyx (referred here to as Site A) and the other at the dimer interface, on the outer surface of the protein between the α-helix and the β-barrel (hereby referred to as Site B) [5,10].…”
Section: Introductionmentioning
confidence: 99%